2010
DOI: 10.1073/pnas.1002155107
|View full text |Cite
|
Sign up to set email alerts
|

Fine analysis of spontaneous MAGE-C1/CT7–specific immunity in melanoma patients

Abstract: Cancer/testis (CT) antigens represent prime candidates for immunotherapy in cancer patients, because their expression is restricted to cancer cells and germ cells of the testis. MAGE-C1/CT7 is a CT antigen that is highly expressed in several types of cancers. Spontaneous occurrence of CT7-specific antibodies was previously detected by SEREX screen in a melanoma patient. However, naturally occurring CT7-specific T-cell responses have thus far not been detected. Peripheral blood mononuclear cells (PBMCs) from 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…These studies confirm and extend the results of Bharat et al, who demonstrated pre-existing CD8 T cell responses to the MAM-A2.1 epitope in breast cancer patients by tetramer and ELISPOT analysis [2]. Pre-existing CD8 T cell responses to shared tumor antigens have been previously described in melanoma patients [3, 11, 20, 26], and for the shared tumor antigens HER2 [8] and NY-ESO-1 [16]. Immunohistochemistry studies in breast and other solid malignancies [1] now suggest that endogenous antitumor CD8 T cell responses are associated with a favorable prognosis [3].…”
Section: Discussionsupporting
confidence: 88%
“…These studies confirm and extend the results of Bharat et al, who demonstrated pre-existing CD8 T cell responses to the MAM-A2.1 epitope in breast cancer patients by tetramer and ELISPOT analysis [2]. Pre-existing CD8 T cell responses to shared tumor antigens have been previously described in melanoma patients [3, 11, 20, 26], and for the shared tumor antigens HER2 [8] and NY-ESO-1 [16]. Immunohistochemistry studies in breast and other solid malignancies [1] now suggest that endogenous antitumor CD8 T cell responses are associated with a favorable prognosis [3].…”
Section: Discussionsupporting
confidence: 88%
“…T-cell stimulation was conducted as described previously (10). Briefly, CD8 þ and CD4 þ T cells were isolated sequentially from PBMCs by positive selection using MACS (Miltenyi Biotech) according to the manufacturer's instructions.…”
Section: Macs Sorting and In Vitro Stimulationmentioning
confidence: 99%
“…''Normally methylated'' genes are physiologically methylated and unexpressed in most tissues of adults, except testicular germ cells. In contrast, they are demethylated and expressed in various types of human cancers [21], and specific ones, such as NY-ESO-1 and MAGE-C1, are expected to be useful as potential targets for cancer immunotherapy [22,23]. The presence of global hypomethylation is associated with increased rates of chromosome recombination and increased incidence of tumor formation [24][25][26].…”
Section: Introductionmentioning
confidence: 99%